Legal Protection for Consumers in Electronic Transactions E-Commerce Shopee - Fawwaz, Shafira Mufiidah; Mustomi, Otom (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2025)
The rapid development of digital has driven the growth of electronic transactions through e-commerce platforms, one of which is Shopee. This platform offers convenience and speed in online buying and selling. However, behind this convenience, there is a potential risk of loss for consumers, such as goods that are not in accordance, late delivery, to fraud by sellers. This raises the issue of the extent of legal protection provided to consumers in electronic transactions on the Shopee platform. This study aims to examine the form of legal protection for consumers in electronic transactions on Shopee and how the dispute resolution mechanism is in legal protection for consumers in Shopee E-commerce transactions and How the Principles of Islamic Law Legal Protection for Consumers in Shopee E-Commerce Transactions. This study uses a normative juridical method, with a statutory approach and literature studies as the main data sources. The analysis was carried out qualitatively by examining laws and regulations, Shopee policies, and case studies related to consumer protection. The results of the study show that Shopee has implemented several consumer protection mechanisms such as an escrow system, a refund service, and a complaint channel. However, there are still shortcomings in the implementation of consumer rights, especially in terms of information transparency and ineffective dispute resolution. The conclusion of this study is that legal protection for consumers in Shopee has a fairly strong basis, but its implementation is not yet optimal. Additional regulations are needed that specifically regulate e-commerce transactions and increase supervision of digital business actors.